How training is encouraging mothers to deliver in health facilities in Ulang, South Sudan - Panom Puok Duoth Kier (South Sudan Medical Journal, 2021)
In South Sudan, health facility delivery coverage is very low despite the presence of health facilities with staff that can conduct deliveries. Some factors like inaccessibility, insecurity, low knowledge of benefits of health facility delivery, poor services, financial challenges, family influence and cultural practices might be some of the reasons that prevent some mothers from delivering in the health facilities.